Evaluation of selected reasons and analysis of the course of delivery accompanied by a partner - Bąk, Beata; Sikorski, Marek; Woźniak, Aleksandra (Medical Studies/Studia Medyczne, 2014)
Introduction : The popularity of family deliveries has been increasing for several years, so it is reasonable to make an evaluation of the factors that influence decisions on choosing this type of delivery as well as an evaluation of the effects of such a decision. Aim of the research : The aim of the research was to define how the age of a woman in labour, her marital status, residence, her and her partner’s education, financial situation, parity, and participation in classes at a childbirth school can affect a decision on having a family delivery. The research also defined the objective indices of the birth-giving process: the method of its completion, the performance of episiotomy, application of painkillers, and the condition of the newborn. The quality of the completed labour was evaluated in the subjective opinions of young mothers. Material and methods: By means of a survey and analysis of medical documentation, 80 women giving birth in the company of their partners were compared with 80 women giving birth in the traditional way. Results : Place of residence, economic status, parity, education, and attendance of a childbirth school are strongly associated with the chosen form of childbirth. Episiotomy was performed more frequently in women who gave birth in the presence of their partners. Newborn babies received similar scores in the Apgar Scale. Painkillers were applied more often in family deliveries than in conventional ones. Conclusions : The main advantages of a family delivery include the feeling of higher self-esteem and safety, and the strengthening of ties between partners. The disadvantages included fear of worsened quality of sexual life.